Baked clay as a fine aggregate to improve the mechanical properties of structural concrete - Chavarria Reyes, Liliana Janet (2021)
In this research named “Baked clay as a fine aggregate to improve the mechanical properties of structural concrete”, it was taken into consideration the relations water/concrete between 0.55 and 0.65 for a resistence to the axial compression of  f´c =210 kg/cm2. In the present investigation it was taken into account that the material is affected by the precense of high concentrations of chlorides and sulfates, because of its high porosity and permeability that make it fragile and weak not recommendable for structures with armed reinforcement. The natural fine aggregate was replaced by baked clay on different proportions (0, 15, 20 and 25%) analyzing the clay chemical properties, as well as the hardened concrete mechanical properties (flexion, tension and compression at 28 days). The outcomes of the trials indicate the viability of using ground baked clay as a fine aggregate in the elaboration of structural concrete, as long as does not exceet 25% of the natural fine aggregate; also the resistances to the flex increased in a 1.5%, to the tension in a 3.2% and a 8.6%  to the axial compression. Key Words: structural concrete; baked clay; fine aggregate; heavy aggregate; mechanical properties; concrete settlement.